Whipple's Disease: Our Own Experience and Review of the Literature. (17th June 2013) - Bureš, Jan; Kopáčová, Marcela; Douda, Tomáš; Bártová, Jolana; Tomš, Jan; Rejchrt, Stanislav; Tachecí, Ilja
Abstract : Whipple's disease is a chronic infectious systemic disease caused by the bacterium Tropheryma whipplei . Nondeforming arthritis is frequently an initial complaint. Gastrointestinal and general symptoms include marked diarrhoea (with serious malabsorption), abdominal pain, prominent weight loss, and low-grade fever. Possible neurologic symptoms (up to 20%) might be associated with worse prognosis. Diagnosis is based on the clinical picture and small intestinal histology revealing foamy macrophages containing periodic-acid-Schiff- (PAS-) positive material. Long-term (up to one year) antibiotic therapy provides a favourable outcome in the vast majority of cases. This paper provides review of the literature and an analysis of our 5 patients recorded within a 20-year period at a tertiary gastroenterology centre. Patients were treated using i.v. penicillin G or amoxicillin-clavulanic acid + i.v. gentamicin for two weeks, followed by p.o. doxycycline (100 mg per day) plus p.o. salazopyrine (3 g per day) for 1 year. Full remission was achieved in all our patients.